Cold Regions Environmental Test of Boot and Similar Footwear. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1980)
This TOP prescribes methods for evaluation of footwear undergoing cold climate testing. It contains procedures for use in evaluation of functional suitability, compatibility with arctic clothing and equipment operation, durability, troop acceptability, maintainability, and safety. It contains facility and instrumentation requirements for the accomplishment of testing. (Author) Supersedes Rept. no. MTP-10-4-006 dated 23 Jun 69, AD-719 259.